Infrared sensors using poly‐Si thin‐film transistors for proximity sensors integrated in smartphone displays. Issue 3 (10th January 2019) - Kito, Katsuya; Kitajima, Shuhei; Matsuda, Tokiyoshi; Inoue, Masahide; Tamura, Mitsuo; Kimura, Mutsumi
Abstract: We have developed infrared sensors using poly‐Si thin‐film transistors (TFTs) for proximity sensors integrated in smartphone displays. Initially, we evaluate the infrared sensitivities of the poly‐Si TFTs, and it is found that a pin‐type TFT is suitable for the infrared sensors. Next, we propose three types of the infrared sensors. First, an analog current detection‐type sensor has a simple structure, and it is found that it can detect presence of a hand. Second, a lock‐in detection‐type sensor has tolerance against ambient light, and it is found that it can detect a target signal under noise signals. Third, a frequency detection‐type sensor has an advantage that only a digital circuit is necessary for detection, and it is found that it can detect the infrared intensity because the oscillation frequency increases monotonically with the intensity. We can utilize these infrared sensors on demand. Abstract : We have developed infrared sensors using poly‐Si thin‐film transistors (TFTs) for proximity sensors integrated in smartphone displays. An analog current detection‐type sensor has a simple structure, and it is found that it can detect presence of a hand, whereas a lock‐in detection‐type sensor has tolerance against ambient light, and it is found that it can detect a target signal under noise signals. A frequency detection‐type sensor has an advantage that only a digital circuit is necessary for detection, and it is found that it can detect the infrared intensity because the oscillation frequency increases monotonically with the intensity.